Celebrity worship among young adult fans: The role of attachment style and conformity - Emirani Nurfaiza; Farhanah Murniasih (Universitas Trunojoyo Madura, 2026)
The rapid growth of digital fandom culture has increased emotional involvement between fans and celebrities, contributing to the emergence of celebrity worship behavior among young adults. This study aimed to examine the influence of attachment style and conformity on celebrity worship among members of Indonesian singer fanbases in Jakarta. A quantitative correlational design was employed involving 201 participants aged 18 to 25 years who were active members of Indonesian singer fan communities. Participants were selected using purposive sampling techniques. Data were collected using the Celebrity Attitude Scale, Attachment Style Questionnaire, and a conformity scale. Construct validity was tested using Confirmatory Factor Analysis (CFA) with LISREL 8.0, while hypothesis testing was conducted using multiple regression analysis with SPSS 25.0. The findings showed that attachment style and conformity simultaneously had a significant influence on celebrity worship and explained 22.1% of the variance in celebrity worship behavior. Among the attachment dimensions, only preoccupied attachment significantly predicted celebrity worship. Within the conformity dimensions, obedience and agreement also showed significant positive effects on celebrity worship. The findings indicate that emotional dependency and conformity within fandom communities contribute to stronger emotional involvement toward celebrities among young adults.